Effectiveness of Using Ice Gel Packs as an Alternative Coolant - Tariza Fairuz; Ayyu Rizkia Nasution; Dewi Pratiwi; Dhea Syah Nazwa Nasution; M. Rizky Fauzan Tampubolon; Nadia Priska; Lisnawaty Simatupang; Moondra Zubir (Indonesian Journal of Chemical Science and Technology (IJCST), 2025)
This research aims to evaluate the effectiveness of ice gel packs based on tapioca flour mixed with natural ingredients such as vinegar, lemon and lime as a cooling alternative. Ice gel pack is made through a process of mixing the ingredients until homogeneous, heating to form a gel, and freezing. Characteristic tests carried out include pH, freezing time, and temperature changes. The research results show that the acidity level of ingredients affects product performance. Ice gel packs with lime have the lowest pH (pH = 2) and show the best ability to maintain cold temperatures, while vinegar with the highest pH (pH = 4) freezes the fastest but is less effective in maintaining temperature. This research proves that a combination of natural ingredients can produce ice gel packs that are environmentally friendly, efficient, and have wide application potential as a modern cooling solution.